ECOTOXICITY OF PLANT IN GORJ - Roxana Gabriela POPA; Irina Ramona PECINGINA (Fiabilitate şi Durabilitate)
Toxic plants, the content of alkaloids, glucozizi, saponins, essential oils and other compounds, are able to cause severe disease in animals. Is influenced by dose toxicity, solubility toxic, health, immunological and physiological status, age, gender, body weight, hereditary resistance species.